The Porto Alegre paradox: social determinants and tuberculosis incidence - Lisiane Morelia Weide Acosta; Sérgio Luiz Bassanesi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: The incidence of tuberculosis (TB) is strongly associated with social and economic factors. The city of Porto Alegre, in the South of Brazil, has one of the highest Human Development Index and Gross Domestic Product per capita of the country. One would expect that the incidence of tuberculosis in such a place were low. However, the city has very high rates of incidence, the highest among Brazilian capitals. This paradox prompted this work, whose objectives were to analyze the spatial distribution of the incidence rate of bacilliferous pulmonary tuberculosis throughout the neighborhoods of Porto Alegre and its association with socioeconomic indicators. METHODS: Ecological non-concurrent cohort study. The units of analysis were the neighborhoods of the city. The average annual incidence of bacilliferous pulmonary tuberculosis for the period 2000 to 2005 and seven socioeconomic variables were analyzed, with information obtained from the IBGE and the Mortality Information System. Spatial techniques and multivariate analyzes were used to check associations. Inequalities were also measured. RESULTS: The spatial distribution of the incidence rate of bacilliferous pulmonary tuberculosis is very similar, i.e., associated with the distribution of socioeconomic factors. The Relative Index of Inequality was 7.9, showing the great difference in the incidence rate between neighborhoods. CONCLUSION: Porto Alegre presents high incidence rates of bacilliferous pulmonary tuberculosis, which distribution through the neighborhoods of the city is associated with socioeconomic factors. The city's high rate is due to the extremely high incidence rates in its poorest neighborhoods. The authors raise hypotheses and suggest interventions.